Monensina e virginiamicina no desempenho e pH ruminal de bovinos confinados com dieta de milho grão inteiro - Dilda Neto, José (2018)
Some food additives like monensin and virginiamycin are used for increasing and improving the production in confinement on high-grain diets. These antimicrobial additives act by modifying the ruminal environment, controlling the grampositive bacteria population, particularly the ones that produce lactic acid, resulting in the decrease of the ruminal pH, causing acidosis, rumenitis, hepatic abscesses, decrease of the productive performance and, in more extreme cases, the death of the animal. They help in stabilizing the animals consumption and diminishing the eating disorders caused by a diet rich on non-structural carbohydrates. Therefore, the goal was to evaluate performance and ruminal pH parameters of confined animals on a whole grain corn based diet (85%) and pellet (15%) with different additives. The evaluated additives were: 30 ppm of monensin sodium (MO), 17 ppm of virginiamycin (VM) and the association 30 ppm MO / 15 ppm VM (MOVM). Two simultaneous experiments were conducted at the Mato Grosso Federal University Experimental Farm, located in the city of Santo Antonio do Leverger - MT. The first experiment evaluated the consumption and ruminal pH of three bovines, non-castrated males, cannulated in the rumen, with an initial average weight of 449.5 kg and average age of 30 months, in a latin square design 3x3 (DQL), kept in individual stalls. No statistical differences were found in regard to the diet consumption (P<0,7411) and ruminal pH (P<0,7356) between the treatments studied. Averages of 1.80% of the carcass weight and 5.61 for the ruminal pH were obtained. However, a quadratic effect (P<0,0001) of time over the ruminal pH numbers was noticed. The second experiment evaluated the productive performance, fecal consistency score and locomotion of 18 non-castrated male bovines with an initial average weight of 314 kg and approximate age of 30 months, disposed in 3 allotments of 6 animals in a completely randomized design (DIC), totalizing 130 days of experiment. A significant difference was noticed (P<0,055) between the VM and MOVM treatments. The VM treatment provided a heavier final body weight, an increase of the total weight, warm carcass weight, and a higher average daily weight gain than the MOVM treatment. On a different note, the isolated MO treatment provided a similar performance to the one noticed on the VM treatment. No differences were noticed between the treatments in regard to the carcass, which has an average value of 52.23%. The isolated usage or association between monensin and virginiamycin provided the animals with a satisfactory performance, considering the great challenge regarding the diet caused by the high presence of corn originated carbohydrates and the absence of forage. The tested additives provided an adequate ruminal environment for the control of metabolic disorders, and for the maintenance of ruminal health. However, the isolated usage of VM or MO in an MGI presents superior results of animal performance if compared to the MOVM association.